Tourism and the environment : a case study of the Vieux Fort area, Saint Lucia, West Indies : draft - Renard, Yves (ECLAC Port of SpainTT, 1985)
Describes the history, economy, land use and the tourist industry of area under study. Discusses its natural and cultural attractions and the relationship between tourism and the environment. Makes recommendations for development of the tourist industry and for the prudent management of the environment.